Self-Control and Impulsive Buying Behavior in Fashion Models - Morits, Krisna kennedhy; Anakaka, Dian lestari; Panis, Marleny P (Journal of Health and Behavioral Science, 2025)
This study aims to determine the effect of self-control on impulsive buying behavior among members of the Timor Creative People Community in Kupang City. In today's digital and consumer era, self-control is one of the critical factors in controlling unplanned purchasing decisions. This study employs a quantitative approach, utilizing a survey method and simple linear regression analysis techniques. The results of the analysis indicate that self-control has a significant negative effect on impulsive buying, as evidenced by a regression coefficient of -0.809 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) of 0.667 indicates that 66.7% of the variation in impulsive buying behavior can be explained by the self-control variable. These findings underscore the critical role of self-control in suppressing impulsive buying tendencies and provide practical implications in managing consumption behavior, especially among creative young people. Abstrak. Masa dewasa awal ditandai dengan eksplorasi identitas dan gaya hidup, termasuk belanja online. Perilaku impulsive buying sering terjadi pada kelompok ini akibat dorongan emosional dan promosi, yang dapat berdampak negatif pada keuangan pribadi. Kontrol diri menjadi faktor penting dalam mengurangi perilaku impulsif. Penelitian ini menganalisis pengaruh kontrol diri terhadap perilaku impulsive buying pada model Komunitas Timor Creative People. Penelitian ini merupakan penelitian dengan menggunakan analisis regresi linear sederhana. Sampel yang digunakan adalah 50 orang model pada model Komunitas Timor Creative People. Hasil penelitian bahwa menunjukkan kontrol diri berpengaruh signifikan (p-value = 0,00<0,05) terhadap perilaku impulsive buying. Uji hipotesis menunjukkan hubungan signifikan antara kontrol diri dan impulsive buying (sig 0,00 < 0,05). Uji korelasi Pearson menunjukkan hubungan sedang (-0,970) dengan arah negatif, berarti semakin tinggi kontrol diri, semakin rendah impulsive buying.